2010
DOI: 10.1063/1.3427527
|View full text |Cite
|
Sign up to set email alerts
|

Electron attachment to sulfur oxyhalides: SOF2, SOCl2, SO2F2, SO2Cl2, and SO2FCl attachment rate coefficients, 300–900 K

Abstract: Electron attachment to SOF(2), SOCl(2), SO(2)F(2), SO(2)FCl, and SO(2)Cl(2) was studied with two flowing-afterglow Langmuir-probe apparatuses over the temperature range 300-900 K. Attachment rate coefficients at 300 K are k(a) = 2.6+/-0.8x10(-10)(SOF(2)), 1.8+/-0.5x10(-8)(SOCl(2)), 4.8+/-0.7x10(-10)(SO(2)F(2)), 2.4+/-0.7x10(-9)(SO(2)Cl(2)), and 2.0+/-0.6x10(-7) cm(3) s(-1)(SO(2)FCl). Arrhenius plots of the data imply activation energies of 56+/-22 meV(SOF(2)), 92+/-40(SO(2)F(2)), 44+/-22 meV(SOCl(2)), and 29+/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 51 publications
(66 reference statements)
0
5
0
Order By: Relevance
“…The SO 2 F 2 – anion is photosensitive, and the intensities of the SO 2 F 2 – bands were significantly reduced upon λ > 220 nm irradiation. On the basis of our B3LYP calculations, the electron affinity for the SO 2 F 2 molecule is 1.71 eV, which is 0.48 eV higher than the values (∼1.23 eV) obtained using the G2 and G3 procedures. , The photon energy provided by λ > 220 nm irradiation is high enough for the detachment of the additional electron in the SO 2 F 2 – anion. Since no other metal-independent absorption was produced upon UV–vis irradiation, it is most likely that neutral SO 2 F 2 is the photodetachment product.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The SO 2 F 2 – anion is photosensitive, and the intensities of the SO 2 F 2 – bands were significantly reduced upon λ > 220 nm irradiation. On the basis of our B3LYP calculations, the electron affinity for the SO 2 F 2 molecule is 1.71 eV, which is 0.48 eV higher than the values (∼1.23 eV) obtained using the G2 and G3 procedures. , The photon energy provided by λ > 220 nm irradiation is high enough for the detachment of the additional electron in the SO 2 F 2 – anion. Since no other metal-independent absorption was produced upon UV–vis irradiation, it is most likely that neutral SO 2 F 2 is the photodetachment product.…”
Section: Resultsmentioning
confidence: 99%
“…Laser ablation of metal targets is an effective method for the generation of charged species such as molecular anions, which can be subsequently trapped and stabilized in an inert cryogenic matrix . A number of molecular anions have been prepared via the reactions of metal atoms and neutral molecules and characterized by infrared spectroscopy. Recent experimental studies of the reactions of laser-ablated metal atoms and SO 2 revealed the formation of SO 2 – in the matrix, , the spectral features of which are the same as those of SO 2 – anion prepared by different methods. , The stabilization of SO 2 – in the matrix suggests that it should be possible to trap the SO 2 F 2 – anion by laser ablation since the electron affinity of SO 2 F 2 is slightly higher than that of SO 2 . In this paper, we present a combined matrix-isolation infrared spectroscopic and theoretical study of the SO 2 F 2 – anion, which was produced via codeposition of SO 2 F 2 with laser-ablated metal atoms, ions, and electrons in argon and neon matrixes.…”
Section: Introductionmentioning
confidence: 99%
“…Among the products, SO 2 F 2 , S 2 F 10 , and SF 4 are highly toxic. HF and SO 2 are corrosive for insulating equipment [11]. Thus, the use and emission of SF 6 should be seriously restricted.…”
Section: Introductionmentioning
confidence: 99%
“…Of these decomposition components, SO 2 F 2 , S 2 F 10 , and SF 4 are highly toxic, and HF and SO 2 are corrosive. 8 The toxic substances will corrode the insulation equipment, resulting in accidents and insulation hazards; these hazards affect the normal and reliable operation of the power system and directly threaten the health of workers.…”
Section: Introductionmentioning
confidence: 99%